Adoption of artificial intelligence applications in higher education - Reyes, Gary; Tolozano-Benites, Roberto; George-Reyes, Carlos; Rumbaut, Dayron; Barzola-Monteses, Julio (Frontiers in Education, 2025)
This study examined the user experience that influences the adoption of artificial intelligence (AI) applications in higher education, focusing on three dimensions: habit, perceived complexity, and perception of adoption. A quantitative, non-experimental, cross-sectional design was applied, using a Likert scale questionnaire administered to 621 university students in Spain, Mexico, and Serbia, selected through convenience sampling. The results revealed that the frequency of regular use of AI tools is positively associated with a lower perception of complexity and a higher assessment of their educational impact. In addition, significant differences were identified between countries and between public and private universities, with the perception of adoption being more favorable in private contexts and in countries with greater technological familiarity. Correlations between dimensions and network and centrality analyses highlighted the structural role of habit as a facilitator of use and positive perception of AI. This evidence showed the need for differentiated strategies that promote the regular integration of AI, reduce perceived barriers, and enhance its educational impact, considering the contextual factors that condition its acceptance and effective use in university settings.